Rural households in a changing climate - Javier Eduardo Báez Ramírez; Dorothy Kronick; Andrew D. Mason (Institute for the Study of Labor (IZA), 2012)
This paper argues that climate change poses two distinct, if related, sets of challenges for poor rural households: challenges related to the increasing frequency and severity of weather shocks and challenges related to long-term shifts in temperature, rainfall patterns, water availability, and other environmental factors. Within this framework, we examine evidence from existing empirical literature to compose an initial picture of household-level strategies for adapting to climate change in rural settings. We find that although households possess numerous strategies for managing climate shocks and shifts, their adaptive capacity is insufficient for the task of maintaining - let alone improving - household welfare. We describe the role of public policy in fortifying the ability of rural households to adapt to a changing climate.
Keywords: Q12; Q54; O13; 330; climate change; rural households; adaptation; risk-coping mechanisms; long-term effects; Klimaveränderung; Ländliche Armut; Kleinbäuerliche Landwirtschaft; Anpassung; Entwicklungsländer